Kedudukan Saksi Wanita Dalam Fiqh Kontemporer - Listyarini, Dyah (Musawa Jurnal Studi Gender dan Islam, 2009)
This paper asserts tha: contextually speaking a woman is equal with a man. This opinion is based on the principles of musawah ad-dinyyah (religious equqlity) and of musawah al-ijtima'iyyah (social equality) without ever questioning their sexes. In interpreting religious texs, therefore we need to take into considerations the historical, social and cultural contexts of the revelation to find their inner spirit. The male superiority in the affair of witness, and also the leadership of men over women should not be seen to be inherent, automatic rights for all men, because the clauses mentioned in the Qur'anic verses showed tha: their distinct right are contingent upon the fulfillment of certain functions; such as liaving broader knowledge and capability to assume responsibility to feed femily member. Therefore when women have attained similar knowledge and capability, they cannot be denied their rights to perform as witnesses.